This study was designed to evaluate the performance of West African dwarf rams subjected to varying degree of treated velvet bean for a period of 12 weeks. The impact of roasted velvet bean (RVB) on the performance by ram and digestibility of the feed was evaluated. In a randomized complete block design, twelve rams aged 12 and 18 months old with initial weight of 13.67- 14.25kg were randomly allotted into 3 treatments on diets A (0% RVB), B (25% RVB) and C (50% RVB). Weight gain, feed intake and feed conversion were measured. Similarly, in the digestibility trial, 3 animals per treatment were placed in metabolic cages for 14 days of stabilization and 5 days of collection. Treatment effects as affected by varying levels of velvet bean was significant for final live weight gain with values varying from 29.86kg(diet B) to 34.20kg (diet C). Also, the mean live weight gain follows the same trend with the highest mean live weight gain obtained for animals on diet C and the least mean live weight for diet B. The result obtained showed a direct relationship between total feed intake and final live weight gain. Since Mucuna pruriens is available in the dry season therefore, utilization at such period will meet dietary requirement of the sheep. (2013)
This study was designed to evaluate the performance of West African dwarf rams subjected to varying degree of treated velvet bean for a period of 12 weeks. The impact of roasted velvet bean (RVB) on the performance by ram and digestibility of the feed was evaluated. In a randomized complete block design, twelve rams aged 12 and 18 months old with initial weight of 13.67- 14.25kg were randomly allotted into 3 treatments on diets A (0% RVB), B (25% RVB) and C (50% RVB). Weight gain, feed intake and feed conversion were measured. Similarly, in the digestibility trial, 3 animals per treatment were placed in metabolic cages for 14 days of stabilization and 5 days of collection. Treatment effects as affected by varying levels of velvet bean was significant for final live weight gain with values varying from 29.86kg(diet B) to 34.20kg (diet C). Also, the mean live weight gain follows the same trend with the highest mean live weight gain obtained for animals on diet C and the least mean live weight for diet B. The result obtained showed a direct relationship between total feed intake and final live weight gain. Since Mucuna pruriens is available in the dry season therefore, utilization at such period will meet dietary requirement of the sheep.